Hubungan Tingkat Self Esteem Dengan Tingkat Kecemasan Pasien Pre Operasi Sectio Caesarea Di RSI Aisyiyah Malang - Intan Azzahra, Helmalia; Bachtiar , Arief; Marsaid; Nataliswati, Tri (Jurnal Keperawatan Muhammadiyah, 2025)
Objective: To identify levels of self-esteem and anxiety, as well as analyze the relationship between self-esteem and anxiety levels in pre-caesarean section patients at RSI Asyiyah Malang. Methods: This type of research is correlational with a cross-sectional design. The population in this study was preoperative caesarean section patients; the sample size was 44 respondents. The sampling technique used was accidental sampling. Data analysis was carried out using the Spearman Rank correlation test. Results: The results of the analysis showed that the majority of patients had low self-esteem and moderate levels of anxiety. There is a significant relationship with value = 0.000 (0.005) and r = -0.557, which means there is a fairly strong relationship in the negative direction, meaning the higher the level of self-esteem, the lower the patient's anxiety level. Conclusion: Patients with low levels of self-esteem are less able to control their emotions when under pressure and overcome their anxiety. Therefore, it is very important to know the level of self-esteem in patients who experience anxiety to determine more appropriate treatment.